Aplikasi Irigasi Tetes pada Budidaya Bunga Telang dan Rosela dalam Rangka Inisiasi Edu-Ekowisata Bukit Cahaya Rangsot - Anjar Pranggawan Azhari; Afifah Farida Jufri; Novita Hidayatun Nufus; Amrul Jihadi; Reni Apriani; Raehanayati Raehanayati (Jurnal Pengabdian Masyarakat Sains Indonesia, 2026)
The Bukit Cahaya area in Rangsot Hamlet, Sigar Penjalin Village, North Lombok, is managed by KSM Cahaya and has the potential to become an edu-ecotourism area based on natural sustainability. One of the development initiatives is the cultivation of edible flowers (rosella and butterfly pea), which require water-efficient irrigation in the form of drip irrigation, given the water scarcity in the region. However, the knowledge and skills of the management and members of KSM Rangsot in installing and maintaining drip irrigation systems are still inadequate. This community service activity aimed to improve the partners' knowledge and skills in operating and maintaining drip irrigation for butterfly pea and rosella cultivation. The methods used are educational (extension and direct demonstration) and participatory (active involvement of partners in all activities). The results show that this activity successfully improved participants' knowledge and skills regarding drip irrigation techniques through direct knowledge transfer and active involvement, while also opening opportunities for applying similar technology to other commodities in the future. The extension and training activities conducted have proven effective in enhancing the capabilities of KSM Rangsot. Suggestions for future activities include the need for periodic mentoring to ensure consistency in technology application, as well as the addition of drip irrigation application materials for other potential commodities in the Bukit Cahaya area, so that the benefits of the activities are broader and more sustainable.